Time Series of Oceanographic Data offshore Prins Karls Forland - Ferré, Benedicte; Dølven, Knut Ola (DataverseNO, 2024)
This time series show oceanographic data collected from an seafloor ocean observatory monitoring a seabed methane seep site offshore West Spitsbergen at around 90m depth. Two datasets are included here: a first deployment from July 2015 to May 2016 and a second from October 2016 to July 2017. Here only temperature, salinity and pressure are given, as well as calculated conservative temperature and absolute salinity. The salinity during the first deployment drifted and a correction is proposed. Temperature, salinity and pressure from the first dataset has been previously published in Dølven et al. 2022 (https://doi.org/10.18710/CEIA1U)